Utilization of Rice Straw Waste in The Production of Crude Cellulase by Aspergillus Niger for Biodeingking Processes - Yanty Maryanty; Kristina Widjayanti; Sri Rulianah; Meiliefiana Meiliefiana; Windra Putri Juwita (IPTEK Journal of Proceedings Series, 2014)
Rice straw is agricultural waste that contains cellulose and has not been used optimally. The agricultural wastes contain cellulose which can be utilized for the production of cellulase enzymes. Cellulase produced from cellulose hydrolysis process in such materials through enzymatic hydrolysis. This study aimed to determine the effect of substrate type and temperature delignification on cellulase enzyme production and determine the effect of the number of additional enzymes of each substrate at biodeinking process. Variable used is the temperature used in the delignification process (100oC and 120oC), the addition of substrate (2,3,4,5,6%), additional doses of the application biodeinking (1,2,3,4,5%). Research conducted by softening rice straw to 30 mesh size media then delignification using 100 ° C and 120 ° C for 150 minutes, and fermented with Aspergillus niger in liquid inoculum, growth curves, and the crude cellulase production. The resulting crude cellulase was applied to the process biodeinking. Fieldwork results showed that at a temperature of 120oC delignification can reduce lignin content in straw was 48.7%. Highest crude cellulase activity of delignification results 120oC 4% resulting from the addition of media on the production of the enzyme activity of crude enzyme with 118.055 units / ml. Biodeinking application results showed that the addition of 3% crude cellulase with medium straw delignification results of 120oC can raise the value of paper brightness of 35.39% to 42.86% or 17:42%.